A study on the asymmetric cylinder wall thickness difference discrimination by dolphins - Feng, Wen; Zhang, Y.; Wei, Chong (ACOUSTICAL SOC AMER AMER INST PHYSICS, 2018)
Atlantic bottlenose dolphins (Tursiops truncatus) can effectively discriminate between water-filled cylinders with different wall thicknesses. The dolphins' performance may be particularly good when the cylinders are thinner. The dolphins' performance is also asymmetric, in that the discrimination accuracy is not equal when the target thickness increases and decreases by the same amount. Inspired by this, a finite element model is proposed here to mimic a dolphin actively transmitting sound to discriminate between targets using acoustic echoes. The waveforms and frequency spectra of acoustic echoes from a standard cylinder and comparison cylinders with wall thickness differences of ±0.3 mm were compared. The employed model simulations show good agreement with previous experimental measurements by Au and Pawloski [(1992). J. Compar. Physiol. A 170(1), 41-47]. Asymmetric arrival time shifts were found for the echo peaks and troughs with the same sequence numbers when the wall thicknesses were increased and decreased by the same amount. This asymmetry became more significant for echo peaks and troughs with higher sequence numbers. Apart from these asymmetric arrival time shifts of the acoustic echoes, the patterns of echo waveforms, the spatial distributions of sound pressures in the water, and the particle vibratory displacements in the cylinders were also found to vary with cylinder thickness. The physical origin of this asymmetric discrimination by the dolphins was explored using both geometric acoustics and wave acoustics. The asymmetry observed might be caused by the circumferential surface (Lamb) wave in the cylinder wall, which is a wave acoustics phenomenon that cannot be derived from geometric acoustics. The findings in this paper might be valuable not just for understanding the mechanism of the effect described, but also for helping the development of biomimetic intelligence for robust signal processing in underwater target discrimination.